The role of frictional power dissipation (as a function of frequency) and test temperature on contact temperature and the subsequent wear behaviour in a stainless steel contact in fretting - Jin, X.; Shipway, P.H.; Sun, W. (Elsevier, 2015)
Temperature is known to affect the fretting wear behaviour of metals; generally, a critical temperature is observed, above which there are substantial reductions in wear rate, with these being associated with the development of protective oxide beds in the fretting contact. This work has examined the gross sliding fretting behaviour of a stainless steel as a function of bulk temperature and fretting frequency(with changes in the fretting frequency altering the frictional power dissipated in the contact amongst other things). An analytical model has been developed which has suggested that at 200 Hz, an increase in the contact temperature of more than 70°C can be expected, associated with the high frictional power dissipation at this frequency (compared to that dissipated at a fretting frequency of 20 Hz). With the bulk temperature at either room temperature or 275°C, the increase in contact temperature does not result in a transition across the critical temperature (and thus fretting behaviour at these temperatures is relatively insensitive to fretting frequency). However, with a bulk temperature of 150°C, the increase in temperature associated with the increased frictional power dissipation at the higher frequency results in the critical temperature being exceeded, and in signiﬁcant differences in fretting behaviour.